Ethnic minority entrepreneurship: An examination of Pakistani entrepreneurs in the UK - Lorna A. Collins; Rebecca Fakoussa (Journal of Innovation and Entrepreneurship, 2015)
This paper discusses the findings from a pilot study which forms part of a larger, on-going study considering the nature of family dynamics in ethnic minority-owned family businesses based in the UK. The paper explains the cultural theoretical framework for the study and highlights some of the cultural aspects identified in one Pakistani family business. Ethnic minority entrepreneurs, including those of Pakistani, Indian, Asian and Caribbean descent, are making significant contributions to UK economic development. Previous studies (JEMS 27(2), 241-258, 2001; http://ssrn.com/abstract=1496219, 1990) have shown that in the UK, the number of ethnic minority start-ups is high compared to other groups. However, the contribution of migrant entrepreneurs has been largely neglected by both entrepreneurship researchers (EURS 11(1), 27-46, 2004; EPGP 7(1), 153-172, 1989) and family business researchers. The unit of study for the investigation is the family. Investigations where the family is the unit of study are relatively unusual in the family business literature, and there have been recent calls for more studies of this type (FBR 22, 216-219, 2009). This study extends the work of (IJEBR 10(1/2), 12-33, 2004) by looking in depth at the impact of culture and family on entrepreneurial aspirations in the context of UK-based, Pakistani, family-owned businesses. The pilot study sought to determine the entrepreneurial nature of Pakistani family businesses based in the UK, focusing particularly on the cultural aspects of the family in order to understand the differences between the Pakistani and UK contexts. This study contributes to our knowledge as it is, as far as the authors are aware, the first case study to focus on the family in a Pakistani family business in the UK SME sector. It not only explores the cultural and individual struggles experienced by the brothers in the family but also exposes the extreme work-life imbalance that exists in small, family-run businesses and demonstrates the effects that this has on all involved. It offers a unique insight into the business culture and personal culture in a Pakistani-owned family firm, thereby casting light on an aspect of British Pakistani life which is currently under-researched.
Keywords: 650; Family business; Ethnic minority; Migrant entrepreneurs; Entrepreneurship; Pakistani